Paradigma Baru Pengembangan Modal Manusia di Era Globalisasi dan Otomasi - Nafisha, Nadya; Ginting, Hilkia Natasya Br.; Manik, Citra Wulandari; Putri, Aulia; Hidayat , Nasrullah; Dalimunthe , Muhammad Bukhori (CV. ULIL ALBAB CORP, 2026)
The era of globalization and automation has brought fundamental changes to the economic structure and work environment. The integration of digital technology, artificial intelligence (AI), and automation in industry has not only increased efficiency but also disrupted work practices and human needs. The purpose of this study is to analyze how the traditional paradigm of human development has been replaced by a new adaptive paradigm, which is in line with the challenges of the Industrial Revolution 4.0 and 5.0. The method used is literature research, which describes various national and international academic sources related to classical human capital theory (Schultz, 1961; Becker, 1964) to modern knowledge economics (Drucker, 1993; Romer, 1990). The results of the study show that human capital development currently involves synergy between technical expertise, digital literacy, critical thinking skills, creativity, cross-field collaboration, and work ethics in a digital environment. This new paradigm emphasizes the importance of lifelong learning, data literacy, and adaptability as the foundation for working effectively in a workplace disrupted by technology. The success of Indonesia's demographic bonus and economic transformation is linked to the ability of the government and educational institutions to improve the education system, increase digital literacy, and strengthen intercultural understanding. This study suggests that human development centered on innovation, creativity, and digital literacy is the primary means of ensuring inclusive and resilient economic growth in the era of globalization and automation.